Design and validation of a cross-cultural virtual exchange experience among bilingual medical students - Vaile, John R.; Doran, Cierrah; Maheu, Arlene R.; Jaramillo, Valentina; Perez-Chadid, Daniela A.; Fernandez, Tomas; Walkosak, Carissa C.; Velez, Dinah Roll; Osorio, Sara Carolina Bedoya; Seebadri-White, Courtney; Truong, Susan; Papanagnou, Dimitrios; et al. (Frontiers in Medicine, 2025)
Exposure to cross-cultural medical education is essential for professionals aiming to work in global health or serve diverse communities. However, traditional in-person exchange programs can be complex, costly, and restricted, particularly during times when travel is limited, such as during the COVID-19 pandemic. These challenges prompted us to explore novel approaches to support cross-cultural exchange programs. We designed, piloted, and evaluated a cross-cultural virtual exchange experience using case-based learning (CBL). Our study involved 14 bilingual medical students from the United States and Colombia who participated in four virtual CBL sessions. Following each session, participants engaged in guided discussions to reflect on their attitudes toward the experience, and content analysis was framed by sociocultural learning theory (SCLT). This study provides justification and operational guidance for implementing and improving upon cross-cultural virtual exchange experiences among medical trainees, with potential applicability to other contexts.